2013
DOI: 10.5194/ms-4-357-2013
|View full text |Cite
|
Sign up to set email alerts
|

On understanding of design problem formulation for compliant mechanisms through topology optimization

Abstract: Abstract. General problems associated with the design of compliant mechanisms through the topology optimization technique are defined in this paper due to the lack of comprehensive definitions for these problems in the literature. Standard design problems associated with rigid body mechanisms, i.e. function generation, path generation and motion generation, are extended to compliant mechanisms. Functional requirements and the associated 25 formulations in the literature are comprehensively reviewed along with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Meanwhile, dual FBGs temperature compensation will be conducted to offset the cross influence of temperature. To improve resolution and accuracy, various types of epoxy will be explored, and optimized nitinol tubular structures will be designed through topology optimization [34,35]. In addition, to secure the contact between nitinol tube and sheath, it is recommended to weld the nitinol tube and sheath as an entire part, which will also further reduce the size of tool connection portion.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, dual FBGs temperature compensation will be conducted to offset the cross influence of temperature. To improve resolution and accuracy, various types of epoxy will be explored, and optimized nitinol tubular structures will be designed through topology optimization [34,35]. In addition, to secure the contact between nitinol tube and sheath, it is recommended to weld the nitinol tube and sheath as an entire part, which will also further reduce the size of tool connection portion.…”
Section: Discussionmentioning
confidence: 99%
“…The so-called kinetostatic formulations, in one form or another, simultaneously aim to maximize the energy transmission between the input and output ports and mechanism's structural stiffness [21]. The mechanism performance is generally quantified using the concepts of mechanical advantage, geometric advantage, mechanical efficiency, flexibility-stiffness or mutual potential energy [24]. Although there is no single universally accepted formulation, it has been shown that these formulations produce almost similar topologies for the optimized compliant mechanisms [17], viz.…”
Section: Kinetostatic Formulationsmentioning
confidence: 99%
“…2 A flexure hinge can be customized to a specific motion; therefore, most of compliant mechanisms are flexure hinge based. 3 Compliant mechanisms with flexure hinges have been applied widely in precision positioning where small displacements are needed in a well-controlled environment. 4 For example, many types of compliant mechanisms have been developed for micro-component assembly in biotechnology.…”
Section: Introductionmentioning
confidence: 99%